2022
DOI: 10.3892/mmr.2022.12731
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of Ginsenoside Re against neurotoxin‑induced Parkinson's disease models via induction of Nrf2

Abstract: The aim of the present study was to examine the neuroprotective effects of a panel of active components of ginseng and to explore their molecular mechanisms of action in two rotenone (Rot)-induced models of Parkinson's disease: An in vitro model using the human neuroblastoma cell line SH-SY5Y and an in vivo model using Drosophila . Ginsenoside Re (Re) was identified as the most potent inhibitor of Rot-induced cytotoxicity in SH-SY5Y cells by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
(43 reference statements)
0
18
0
Order By: Relevance
“…The main active compounds in ginseng include ginsenosides, polysaccharides, and polypeptides, among others (Ratan et al, 2020 ). Ginsenosides are important saponins, and it is precise because of those compounds that ginseng is highly valued (Qiao et al, 2022 ). The quality of ginseng medicinal materials is closely related to ginsenoside monomer and total ginsenoside contents in rhizomes.…”
Section: Introductionmentioning
confidence: 99%
“…The main active compounds in ginseng include ginsenosides, polysaccharides, and polypeptides, among others (Ratan et al, 2020 ). Ginsenosides are important saponins, and it is precise because of those compounds that ginseng is highly valued (Qiao et al, 2022 ). The quality of ginseng medicinal materials is closely related to ginsenoside monomer and total ginsenoside contents in rhizomes.…”
Section: Introductionmentioning
confidence: 99%
“…The results were consistent with previous reports that the antioxidant and hepatoprotective effects of ginsenoside Rg1 are mainly achieved through induction of the Keap1-Nrf2-ARE signaling pathway ( Gao et al, 2017 ). Wang et al also reported that Re protects neurons from oxidative damage at least in part through induction of the Nrf2/HO-1 pathway ( Qiao et al, 2022 ). Therefore, we hypothesized that ginsenosides Rg1 and Re ameliorated LPS-mediated oxidative stress injury in broilers by mediating the Keap1-Nrf2-ARE pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another experiment with Re (5 μM), but in a PD model with rotenone-intoxicated SH-SY5Y cells, evidenced the same action on viability, apoptosis, and activation of Nrf2 and genes governed by it despite using a lower concentration of the compound. Furthermore, it was concluded that Nrf2 activation occurred through Re stimulation of the PI3K/Akt/Nrf2 and p-ERK/Nrf2 pathways [ 85 ]. On the other hand, in vivo assays have been performed with mice with memory deficits caused by chronic restraint stress.…”
Section: Terpenoidsmentioning
confidence: 99%